Assessment of detection methods for the endangered Amargosa vole - Austin Roy; Arielle Crews; Stephanie Castle; Robert Klinger; Deana Clifford; Janet Foley (California Fish and Wildlife Journal)
Understanding which detection methods to use is important to endangered species research and management and often requires a balance between costs and benefits. We investigated the efficiency and costs of camera-trapping, live-trapping, and sign surveys (vole feces, clippings, runways) as methods for detection of the endangered Amargosa voles (Microtus californicus scirpensis). Although each method documented the presence of voles, baited camera-trapping was the most sensitive method for detecting voles and provided insights into vole activity and behavior. Although live-trapping had 100% specificity and provided data and access to biological samples that could not be collected through other methods, it had reduced sensitivity (85.2%) compared to camera-traps and incurred potential risk to individual voles. Sign surveys were the least sensitive method (78.9%) and suffered in that some types of sign could not accurately be attributed to species. Additionally, sign surveys could not inform about how recently vole activity had occurred because Amargosa vole feces can persist in the environment for long periods of time and degrade 4.7 times faster in wetter marshes than dryer sites. Sign and fecal surveys are best suited for occupancy and distribution surveys at a coarse time scale (≥1-year intervals) but are likely to have low predictive values in years when vole abundance is low. Cost comparisons indicate the highest per session cost and moderate habitat impact for camera trapping, highest overall cost and highest impact to habitat for live-trapping, and lowest expense and habitat impact for sign surveys but relatively low yield in data quality.